Validity and reliability of the Turkish version of breathlessness beliefs questionnaire. (3rd April 2023) - Gurses, Hulya Nilgun; Saka, Seda; Zeren, Melih; Bayram, Mehmet
ABSTRACT: Background: Dyspnea is often the main symptom that limits exercise; however, the vicious cycle of dyspnea limiting exercise participation is also an important contributor to the reduced exercise capacity. Objective: The aim of our study was to investigate the reliability and validity of Turkish Breathlessness Beliefs Questionnaire (BBQ) in patients with Chronic Obstructive Pulmonary Diseases (COPD). Methods: Seventy-seven COPD patients were included in the study. Sociodemographic and physical characteristics were recorded. Turkish version of BBQ, Saint George Respiratory Questionnaire (SGRQ) and Hospital Anxiety and Depression Scale (HADS) were applied. Second evaluation of BBQ was conducted via telephone calls with no drop-outs. Reliability of the questionnaire was explored by calculating the internal consistency and test–retest analysis. Construct validity was assessed calculating correlation coefficients of BBQ with HADS and SGRQ scores. Known group validity was also explored. Results: Cronbach alpha coefficients for total score of BBQ were 0.78, indicating that the questionnaire has 'good' internal consistency. Initial and test–retest BBQ total scores were 41.42 ± 6.47 and 41.18 ± 6.24, respectively. Intra-class correlation coefficients (ICC2, 1 ) values of BBQ and its sub-scales varied between 0.973 and 0.983, indicating strong test–retest reliability. Correlation coefficient between BBQ total and SGRQ-Activity (0.619) was highest among the variables of interest, followed by BBQ total and SGRQ total (0.611). There was a significant correlation between BBQ total and HADS (0.390). One-way analysis of variance revealed that BBQ total and BBQ-Activity Avoidance scores were significantly differ in disease stages. Conclusion: Turkish version of BBQ was found to be a valid and reliable tool for measuring dysfunctional beliefs related to the dyspnea in patients with COPD.